THE ROLE OF SHARIA COMPLIANCE ON ISLAMIC SOCIAL REPORTING DISCLOSURE OF ISLAMIC BANKS IN INDONESIA - indra siswanti; Retno Purwani Setyaningrum (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study is to examine the effects of the sharia supervisory board (SSB), financial performance, and sharia compliance on Islamic social reporting (ISR) disclosure. This study is a quantitative study that collected data from annual reports from 2015-2020, which was obtained directly from the website of the Islamic banks. EViews version 10 was used to process the data. The study population was 14 Islamic banks in Indonesia, based on the purposive sampling, 9 Islamic banks were used as a sample. The research finding are: 1) sharia supervisory board has no effect on Islamic social reporting disclosure, 2) financial performance has a positive effect on Islamic social reporting disclosure, 3) sharia compliance moderated effect of the sharia supervisory board on Islamic social reporting disclosure, and 4) sharia compliance moderated effect of financial performance on Islamic social reporting disclosure. The existence of the sharia compliance principle would have an impact on the supervision of sharia supervisory board so that there were no violations of sharia principles in the operational activities. Islamic banks has to maintain their reputation through compliance with sharia principles which could improve the performance of Islamic banks in Indonesia. The interaction of financial performance with sharia compliance and sharia supervisory board with sharia compliance would increase the level of Islamic social reporting disclosure. Other researchers need to conduct research on Islamic social reporting disclosure using more diverse independent variables and more quantity of samples to generalize the result to all types of banks.